The Political Economy of Euro-Mediterranean Relations - Kourtelis, Christos. author. aut Link
XII, 123 p.
Keywords: The author analyses the implementation of the agricultural and industrial parts of the European Neighbourhood Policy (ENP) in Egypt, Tunisia and Morocco. Following a sectoral approach to assess the implementation of the ENP, he investigates which interest groups win and which lose from the policy.